2019
DOI: 10.33423/jabe.v21i4.2132
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Productivity in the 2020s: Time for a New E/RA A Research Study on the Impact of Organizational Design and Employee Engagement on the Knowledge Productivity of Service Firms

Abstract: ÿ ÿ kGS[OU RI l ÿ mU \XTQ _ XN Q OTXW ÿ nGI Q \Ta ÿ e`VW OSGGÿ eT\X\G`GTN a ÿ kTO[W GR\Gÿ oU ORJMN Q YQ N Sa ÿ kTO[W GR\Gÿ pGU YQ MGÿ qQ ÙI ] ÿ =73:?ADr3=?7ÿ stÿ 2 ÿ 18 ÿ 13 u54 v5w 14 ÿ x w tÿ 54yÿ z41x6 uÿ x13 z3 { ÿ 2tÿ 5 ÿ 6 5xÿ 8 3 { ÿ 4 23 54ÿ 154 ÿ 54ÿ 5124w 4uÿ 8 3 { ÿ ÿ 5 2ÿ w 1ÿ |ÿ 4 4uÿ 14ÿ w tÿ }256 w y{ ÿ 3 8 13 54ÿ 54ÿ 4u5u4w ÿ 18 ÿ w tÿ z41x6 uÿ x13 z3 ÿ w t6 ÿ 5~413 w { ÿ ÿ 5~413 w ÿ ÿ 3 2 5z{ ÿ ÿ 3 2z3 { ÿ ÿ 5 w 3 { ÿ ÿ5y 14{ ÿ ÿ 4w v|3 u{ ÿ ÿ5 w 3 { ÿ ÿs1ÿ}21w ÿ5~413 w ÿ ÿ 4ÿw tÿ23 3 4w ÿ 141… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Hence, a good P-O fit tends to foster employees' work engagement as previous research has shown (e.g. Kodden & Van Ingen, 2019). In the present study, P-OP fit is a value-congruence type of P-O fit.…”
Section: The Mediating Role Of Person-organizational Purpose (P-op) Fit In the Relationship Between Perceived Organizational Purpose And supporting
confidence: 69%
“…Hence, a good P-O fit tends to foster employees' work engagement as previous research has shown (e.g. Kodden & Van Ingen, 2019). In the present study, P-OP fit is a value-congruence type of P-O fit.…”
Section: The Mediating Role Of Person-organizational Purpose (P-op) Fit In the Relationship Between Perceived Organizational Purpose And supporting
confidence: 69%
“…Work engagement increases among employees who find their work fun, satisfying and interesting (e.g., Kodden & Van Ingen, 2019;Breevaat, Bakker, Demerouti, & Derks, 2016;Nijhuis, van Beek, Taris, & Schaufeli, 2012). According to Kahn (1990), this meaningfulness lies in the type of work, division of roles and interactions within the work.…”
Section: Non-conformism As a Mediating Factor Between Leadership Styl...mentioning
confidence: 99%
“…The role of teachers in students' success, the educational system, and society in the broadest sense is crucial (Keiler 2018;Vesely et al 2013). Therefore, it is of the utmost importance to further research factors that are generally known to influence teachers' well-being at their jobs, such as self-efficacy (Consiglio et al 2013;Skaalvik and Skaalvik 2014;Ventura et al 2015;Kodden and van Ingen 2019), positive emotions (Bondarenko 2017;Schaufeli and Van Rhenen 2006), work engagement and burnout (Bakker and Demerouti 2008Kodden and Groenveld 2019). The well-being of schoolteachers is a broad concept, but in the work situation it can be associated with affects, such as emotions and moods arising from experiences during work (Bianchi et al 2019;Hakanen et al 2019;Holt-Lunstad et al 2015).…”
mentioning
confidence: 99%